2020
DOI: 10.1101/2020.05.12.090308
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Individual reversible plasticity as a genotype-level bet-hedging strategy

Abstract: Reversible plasticity in phenotypic traits allows organisms to cope with environmental variation within lifetimes, but costs of plasticity may limit just how well the phenotype matches the environmental optimum.An additional adaptive advantage of plasticity might be to reduce fitness variance, or bet-hedging to maximize geometric (rather than simply arithmetic) mean fitness. Here we model the evolution of reaction norm slopes, with increasing costs as the slope or degree of plasticity increases. We find that g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Traditionally, conservative bet-hedging has thus been interpreted as a production of generalist phenotypes, suited for an average environment (Philippi & Seger, 1989). However, phenotypic plasticity should, in some cases, also be considered a type of conservative bethedging (Haaland et al ., 2021). This occurs when plasticity results in lower variance in fitness (due to the canalization of fitness) and, at the same time, lower expected arithmetic fitness but higher geometric mean fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, conservative bet-hedging has thus been interpreted as a production of generalist phenotypes, suited for an average environment (Philippi & Seger, 1989). However, phenotypic plasticity should, in some cases, also be considered a type of conservative bethedging (Haaland et al ., 2021). This occurs when plasticity results in lower variance in fitness (due to the canalization of fitness) and, at the same time, lower expected arithmetic fitness but higher geometric mean fitness.…”
Section: Discussionmentioning
confidence: 99%
“…2012). Recently, the combination of phenotypic plasticity and bet-hedging has been theoretically investigated, suggesting that phenotypic plasticity could further minimize fitness variances caused by mismatches between phenotype and environment (Rádai 2020; Haaland et al . 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that the Parsley Frog successfully exploits two temporal niches in the Mediterranean region thanks to a high phenotypic plasticity of tadpole development to face very different seasonal environments (Jourdan-Pineau et al, 2012). Recently, the combination of phenotypic plasticity and bet-hedging has been theoretically investigated, suggesting that phenotypic plasticity could further minimize fitness variances caused by mismatches between phenotype and environment (Rádai, 2020; Haaland et al, 2021). Interestingly, in the wolf spider, temperature and day length leads to alternative developmental types within broods.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a fraction of seeds may germinate in response to good germination rains, but the remaining seeds stay dormant as a hedge against the risk that good germination rains may be followed by unfavorable conditions (Cohen, 1967; Gremer et al ., 2016). On the contrary, plasticity may itself be a bet‐hedging strategy if a genotype produces offspring with different levels of plasticity (Haaland et al ., 2021). Thus, we may see a combination of modes evolve and plants may be particularly effective at combining strategies.…”
Section: Responses To Environmental Variation Depend On Scale and Pre...mentioning
confidence: 99%